Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$(X'+Y )(X+Y')=XY+X'Y'$$

I am just wondering how these are equal, and what laws are used to get there

share|cite|improve this question
up vote 3 down vote accepted

$$ (X'+Y)(X+Y') = XX'+X'Y'+XY+YY' \\ \begin{array}{cl} XX' = 0 & \text{by definition of negation} \\ YY' = 0 & \text{same} \end{array} \\ $$ so $$ (X'+Y)(X+Y') = XY+X'Y' $$ In classical notation it looks like $$ (\neg x \vee y)\wedge(x \vee \neg y) = (\neg x \wedge x )\vee (\neg x \wedge \neg y) \vee (y \wedge x) \vee (y \wedge \neg y) = 0\vee (\neg x \wedge \neg y) \vee (x \wedge y)\vee 0 = \\ = (\neg x \wedge \neg y) \vee (x \wedge y) $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.